The tellurium redox immunomodulating compound AS101 inhibits IL-1β-activated inflammation in the human retinal pigment epithelium. Issue 7 (27th April 2013) - Ling, Diamond; Liu, Baoying; Jawad, Shayma; Thompson, Ian A; Nagineni, Chandrasekharam N; Dailey, Jennifer; Chien, Jason; Sredni, Benjamin; Nussenblatt, Robert B
Abstract : Purpose: AS101 is a non-toxic organotellurium-IV compound with demonstrated immunomodulating activity in vitro and in vivo. Inflammatory responses are attributed to the pathophysiology of numerous ocular diseases. In this study, we wished to elucidate whether AS101 could mitigate pro-inflammatory activity in human retinal pigment epithelial (RPE) cells, which are heavily involved in ocular immune responses, induced by pro-inflammatory IL-β activity. Methods: Primary and transformed RPE cells treated with varying concentrations of AS101 were used in this study. Real-time PCR and ELISA assays were used to detect cytokine/chemokine mRNA expression and protein production. Western blot was used to detect changes in the NFκB pathway. Cell viability and proliferation were detected using a Vi-Cell XR cell counter. To measure the cytoprotective capacity of AS101, cell numbers were compared between cells treated with IL-1β or lipopolysaccharide (LPS) and cells treated with IL-1β or LPS in the presence of AS101. Results: AS101 inhibited IL-1β-induced mRNA expression and protein production of IL-6 and IL-8 in RPE cells. The viability of RPE cells treated with IL-1β and LPS was unaffected. AS101 slightly inhibited RPE cell growth in the presence of higher levels of IL-1β. Also, AS101 downregulated the IL-1β activity by inhibiting the phosphorylation of p65, an NFκB subunit. Conclusions: The results demonstrate that AS101 reduces IL-1β-induced inflammatory responses in the RPE. In previous studies, AS101 exhibited therapeutic effects in various disease models and was a safe profile in clinical trials. These results suggest that AS101 may have potent anti-inflammatory potential in the eye and confer the downregulation of RPE inflammatory responses in a pathological environment.